Preoperative nomogram predicting ventriculoperitoneal shunt longevity after initial shunt failure - Liu, Dongsheng; He, Qiheng; Niu, Jianxing; Li, Liangliang; Geng, Ronghua; Cao, Tianqing; Wang, Xiaosong; Lv, Zeping; He, Jianghong; Zhao, Jizong; Chen, Guoqiang; Yang, Yi (Frontiers in Neurology, 2024)
Background and objectives Initial shunt failure following ventriculoperitoneal (VP) shunt surgery has a significant impact on the working time of the shunt. However, there are few studies regarding factors affecting VP shunt longevity. Hence, in this study, we aimed to build a nomogram to predict the longevity of the replacement VP shunt in patients with initial shunt failure. Methods From 2011 to 2021, 142 patients with initial VP failure who underwent VP shunt revision were enrolled and relevant clinical and demographic factors were analyzed. Univariate and multivariate Cox proportional hazard regression models were used to choose predictors, and a nomogram was constructed using nine independent prognostic variables: sex, age, hydrocephalus type, intensive care unit admission, tracheostomy, decompressive craniectomy, craniotomy, lumbar cisterna drainage, and ventricular drainage. The prediction models’ discrimination, accuracy, calibration, and clinical value were evaluated using Harrell’s C-index, a calibration plot, and decision curve analysis. Results At 1 month, 3 months, and 5 years, the nomogram’s C-index was 0.680, 0.708, and 0.694, respectively. The nomogram’s calibration plot provided a good fit for the overall prediction over the course of 1 year. Decision curve analysis predicted that 1–3 months after surgery will yield good net benefits between 30 and 50% probability thresholds. Conclusion A preoperative nomogram may be an effective tool for assessing VP shunt longevity after initial VP shunt placement.